Media Framing and Framing by Politicians - ISEP YAHYA (Universitas Muhammadiyah Yogyakarta, 2019)
There are substantial amount of academic research regarding to how media do the framing on certain issue. However, empirical research on the framing interactions is still difficult to find. This study endeavors to fill the void by questioning the mutual influences between media framing and framing by politicians on a specific issue during the political campaign ahead of 2017 Jakarta Governor Election. Both quantitative and qualitative content analysis methods were employed in this research. First of all, textual data from the media and politicians were coded using Atlas.ti coding software in order to know the usage of five framing types: conflict, morality, economic consequences, responsibility and human interest. After that, the mutual influence was investigated by looking at their most dominant frames, their comparative trends in terms of framing quantity, and their textual interactions. This research then reveals a weak mutual influence between media framing and framing by politicians. It is indicated from their differences in using dominant frames. Conflict consistently dominated media framing, while economic consequences were generally dominant within politician’s framing. Besides, media and politicians produced different quantity of framing and presented different trends. Media and politicians also presented an insignificant textual interactions by sharing small number of similar keywords and mutual quotations.